Las relaciones interpersonales y el comportamiento organizacional en los servidores públicos del GAD cantonal de Junín – periodo diciembre 2021 – junio 2022 - Delgado Macias, Michael Francisco (2023)
The main objective of the research was to evaluate the interpersonal relationships and the organizational behavior of the public servants of the Municipal GAD in Junín canton and the impact that these generate, the work had 3 phases, in the first phase an interview was conducted with the head of the human talent department, then an observation guide was carried out that allowed to perceive in the first person what the work environment is like within the institution. In the second phase, it was designed to apply and tabulate a survey of all employees, in this way it was possible to obtain direct information from those involved. In the last phase, with allthe collected material, a matrix was prepared that contains an action plan in order to improve the links between employees.